Teaching Beam Sizing Concepts Using the Experimental Process - Steffen, Richard W.; Watson, Dennis G.; Harrison, Tony V. (Journal of Agricultural Systems, Technology, and Management, 2004)
A student laboratory activity was developed that uses the experimental process to test the failure point of miniature wooden beams. This lab is used to introduce the variables that influence beam strength to the students in an introductory agricultural systems class. The laboratory activity also gives the students an opportunity to practice the experimental process and their communication skills.